Engraved Clerical Portraiture in England, c. 1660–1850: An Introductory Survey. Issue 1 (10th May 2021) - Sharp, Richard
Abstract : Architecture and visual arts in general have been subjects of a growing body of recent scholarship connected with the ecclesiastical history of the 'Long Eighteenth Century', but little attention has been given to portraiture. Although honourable mention should be made of pioneering work by John Ingamells on painted episcopal portraits, and by Peter Forsaith, very recently, on Methodist portrait prints, other aspects of this extensive subject still await investigation. The article outlines the development of engraved portrayal of clergy, mainly of the Church of England, during the two centuries before production of multiple images was taken over by photography, and indicates how the quantity, variety, and dissemination of such material can provide some index of the priorities of a pre-photographic age. It does not aim to be a comprehensive or a complete survey of the corpus of engraved portraiture; nevertheless, this article provides an initial guide to the abundance of previously unexplored illustrative material, and may suggest a framework for further exploration. It is hoped that future scholars will build on this initial work to enable a complete catalogue of such images to be developed and further explored.